Synthesis, Antimicrobial Evaluation and In silico Studies of Novel 2,4- disubstituted-1,3-thiazole Derivatives - Masood, Mir M.; Irfan, Mohammad; Alam, Shadab; Hasan, Phool; Queen, Aarfa; Shahid, Shifa; Zahid, Muhammad; Azam, Amir; Abid, Mohammad (Letters in Drug Design & Discovery, 2019)
Background: 2,4-disubstituted-1,3-thiazole derivatives (2a–j), (3a–f) and (4a–f) were synthesized, characterized and screened for their potential as antimicrobial agents. In the preliminary screening against a panel of bacterial strains, nine compounds showed moderate to potent antibacterial activity (IC50 = 13.7-90.8 μg/ml). Methods: In the antifungal screening, compound (4c) displayed potent antifungal activity (IC50 = 26.5 μg/ml) against Candida tropicalis comparable to the standard drug, fluconazole (IC50 = 10.5 μg/ml). Based on in vitro antimicrobial results, compounds 2f, 4c and 4e were selected for further pharmacological investigations. Hemolytic activity using human red blood cells (hRBCs) and cytotoxicity by MTT assay on human embryonic kidney (HEK-293) cells revealed non-toxic nature of the selected compounds (2f, 4c and 4e). To ascertain their possible mode of action, docking studies with the lead inhibitors (2f, 4c and 4e) were performed using crystal structure coordinates of bacterial methionine aminopeptidases (MetAPs), an enzyme involved in bacterial protein synthesis and maturation. Results: The results of in vitro and in silico studies provide a rationale for selected compounds (2f, 4c and 4e) to be carried forward for further structural modifications and structure-activity relationship (SAR) studies against these bacterial infections. Conclusion: The study suggested binding with one or more key amino acid residues in the active site of Streptococcus pneumoniae MetAP (SpMetAP) and Escherichia coli MetAP (EcMetAP). In silico physicochemical properties using QikProp confirmed their drug likeliness.
Keywords: cytotoxicity